BEREJUNG: DINAMIKA TRANSISINYA DALAM KONTEKS SOSIAL BUDAYA - Neisya, Neisya; Rosmaidar, Rosmaidar; Ramadhani, Rizqi (Jurnal Ilmiah Bina Bahasa, 2017)
Abstract :Oral literature is one of the most important part in the existence of regional literature, including the province of South Sumatra. However, this type of literature began to be less enjoyed because it is considered outdated and not in accordance with the tastes of today's society. Not surprisingly, the number of its lovers began to decrease and leaving only the old people. This research highlights about oral literature Berejung owned by Besemah tribe of Pagaralam, South Sumatera which experienced the same thing. The aim is to see the dynamics of change or transition of the oral literature Berejung from the first to present form of presentation. Sources of data were obtained by using direct observation methods and interviews with related parties, such as speakers and art activists. The results of field research indicate that oral literature Berejung has undergone several transitions from spoken directly through the mouth, followed by the lute and the sole guitar and the last in a musical orchestra.